STRATEGIC DETERMINANTS OF COMPETITIVENESS OF WOOD PROCESSING INDUSTRY ENTERPRISES IN A DYNAMIC ENVIRONMENT - PAKHUCHA, Ellina; IVASHCHENKO, Vyacheslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the strategic determinants that shape the competitiveness of enterprises in the wood processing industry within a dynamic and volatile business environment. The study emphasizes the growing importance of identifying, evaluating, and managing those determinants that directly influence the ability of enterprises to operate sustainably and maintain stable market positions. The research identifies a wide range of factors that affect competitiveness, including the availability and efficiency of using raw materials, the organization of production processes, the quality of managerial decision-making, financial resilience, technological development, market presence, and compliance with ecological and social requirements.The article analyzes the specific challenges faced by wood processing enterprises, such as instability of timber supply chains, fluctuations in global market demand, increasing competition from imported products, and stricter environmental regulations. It is demonstrated that the development of the industry is increasingly dependent on the implementation of advanced technologies, improvement of logistics processes, involvement in sustainable forest management systems, and alignment of production activities with the principles of the circular and green economy. A significant conclusion arising from the study is that competitiveness in this sector cannot be ensured solely through price advantages; it must be based on innovation, strategic flexibility, diversification of products and markets, and long-term investment priorities. Based on the findings, the article develops a comprehensive model of strategic determinants of competitiveness, reflecting the interrelation between production capacities, managerial efficiency, technological modernization, marketing capabilities, financial stability, socio-environmental responsibility, and the institutional environment. This model can serve as a methodological framework for enterprises, enabling them to monitor competitiveness indicators, anticipate risks, optimize resource allocation, and build adaptive development strategies. The study concludes that strengthening the competitiveness of wood processing enterprises requires not only technological upgrading and resource efficiency improvements but also the development of proactive strategies aimed at innovation management, value-added product creation, environmental compliance, and market expansion. The research results provide a foundation for further analytical and empirical studies aimed at improving assessment tools, developing industry-specific competitiveness indices, and designing policy recommendations to support sustainable development of the wood processing industry.
Keywords: enterprise competitiveness; strategic determinants; woodworking industry; risks; innovative development; competitive advantages; market environment; strategic management